On the roles of AA15 lytic polysaccharide monooxygenases derived from the termite Coptotermes gestroi - Franco Cairo, João Paulo L.; Cannella, David; Oliveira, Leandro C. [UNESP]; Gonçalves, Thiago A.; Rubio, Marcelo V.; Terrasan, Cesar R.F.; Tramontina, Robson; Mofatto, Luciana S.; Carazzolle, Marcelo F.; Garcia, Wanius; Felby, Claus; Damasio, André; et al. (My University, 2021)
Lytic polysaccharide monooxygenases (LPMOs) are copper-dependent enzymes which catalyze the oxidative cleavage of polysaccharides. LPMOs belonging to family 15 in the Auxiliary Activity (AA) class from the Carbohydrate-Active Enzyme database are found widespread across the Tree of Life, including viruses, algae, oomycetes and animals. Recently, two AA15s from the firebrat Thermobia domestica were reported to have oxidative activity, one towards cellulose or chitin and the other towards chitin, signalling that AA15 LPMOs from insects potentially have different biochemical functions. Herein, we report the identification and characterization of two family AA15 members from the lower termite Coptotermes gestroi. Addition of Cu(II) to CgAA15a or CgAA15b had a thermostabilizing effect on both. Using ascorbate and O2 as co-substrates, CgAA15a and CgAA15b were able to oxidize chitin, but showed no activity on celluloses, xylan, xyloglucan and starch. Structural models indicate that the LPMOs from C. gestroi (CgAA15a/CgAA15b) have a similar fold but exhibit key differences in the catalytic site residues when compared to the cellulose/chitin-active LPMO from T. domestica (TdAA15a), especially the presence of a non-coordinating phenylalanine nearby the Cu ion in CgAA15a/b, which appears as a tyrosine in the active site of TdAA15a. Despite the overall similarity in protein folds, however, mutation of the active site phenylalanine in CgAA15a to a tyrosine did not expanded the enzymatic specificity from chitin to cellulose. Our data show that CgAA15a/b enzymes are likely not involved in lignocellulose digestion but might play a role in termite developmental processes as well as on chitin and nitrogen metabolisms.
Keywords: AA15; CAZymes; Chitin; Chitinases; LPMOs; Termites